Developing Life Skill Based English Instructional Material in Bilingual Pesantren - Febria Sri Artika; Widya Syafitri; Risdaneva Risdaneva (AT-TA'LIM, 2020)
This study is aimed at developing life skill based English instructional material in bilingual pesantren by using 4D Model (Define, Design, Develop, and Disseminate). To achieve this aim, this study was conducted using the Research Development (R d) method. As parts of this method, a series of data collecting techniques involving pre-experimental teaching, interviews, observations, and tests of effectiveness, practicality and validity, were carried out to gather both quantitative and qualitative data. The participants of this study were one English language teacher and students of Class XI Timur Tengah, Insan Cendikia Boarding School (ICBS) Payakumbuh. The findings of this research reveal that the life skill based instructional material is valid and practical. Consequently, the life skill-based materials development can positively give the effective result as the innovation in English instructional material